Aggravation of symptomatic occipital epilepsy of childhood by carbamazepine - Škrijelj, Fadil E; Mulić, Mersudin (Vojnosanitetski pregled, 2014)
Introduction. Carbamazepine can lead to aggravation of epileptic seizures in generalized epilepsies (primary or secondary) with clinical manifestations of absence (typical or atypical) and/or myoclonic seizures. However, some focal epilepsies can be also aggravated by the introduction of carbamazepine. Case report. We presented a 10-year-old boy born after a complicated and prolonged delivery completed by vacuum extraction, of early psychomotor development within normal limits. At the age of 8 years he had the first epileptic seizure of simple occipital type with generalization and urination. Brain magnetic resonance imaging (MRI) showed focal cortical reductions in the left parietal and occipital regions. Interictal EEG recorded slowed basic activities above the posterior regions of the left hemisphere, with intermittent occurrence of occipital sharp waves and bioccipital sharp and slow-wave complexes. Initially, treatment with valproate was administered; however, the addition of carbamazepine into therapy induced aggravation of seizures and EEG findings, changed behavior and poor performance at school. By withdrawal of carbamazepine the condition improved both clinically and in EEG findings. Conclusion. Childhood occipital epilepsy lesions show deterioration due to carbamazepine, which if administered induces aggravation of seizures, behavior changes, cognition with occurrence of long-term bilateral discharges, and posterior sharp and slow-wave high amplitude complexes recorded by EEG.